2006
DOI: 10.2118/89422-pa
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Upscaling of Two-Phase Flow: From Core to Simulation Scale

Abstract: Summary In the coarse-scale simulation of heterogeneous reservoirs, effective or upscaled flow functions (e.g., oil and water relative permeability and capillary pressure) can be used to represent heterogeneities at subgrid scales. The effective relative permeability is typically upscaled along with absolute permeability from a geocellular model. However, if no subgeocellular-scale information is included, the potentially important effects of smaller-scale heterogeneities (on the centimeter t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Using a two-step upscaling approach reduced the computational costs and made it possible to perform a REV study. This kind of methods has also been used for two-phase flow in heterogeneous reservoirs [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Using a two-step upscaling approach reduced the computational costs and made it possible to perform a REV study. This kind of methods has also been used for two-phase flow in heterogeneous reservoirs [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a speedup factor of over 6,000 that we obtain for the Case 4 study in the presence of the capillary pressure is a demonstration of the method's high efficiency. Lohne et al [54] proposed a two-stage upscaling method for two-phase flows from core to simulation scale, arguing that heterogeneities in the sub-geological scales (centimeter to meter scale) may have a significant effect on flow in a reservoir which cannot be captured if the upscaling starts at the geostatistical scale. They computed the effective properties for the geological units at the geostatistical scale by starting the upscaling at a small scale.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is usually observed that at relatively small scales capillary forces dominate the displacement process, while viscous and gravitational forces may become more important at larger scales (Odsaeter et al 2015;Kumar and Jerauld 1996;Jonoud and Jackson 2008a). Numerous upscaling methods are available in the literature for two-phase flow (Guzman et al 1999;Jacks et al 1973;Kyte and Berry 1975;Stone 1991;Pickup and Sorbie 1996;Lohne et al 2006;Virnovsky et al 2004;King 1989;King et al 1993;Coll et al 2001;Wallstrom et al 2002;Durlofsky 1997) among which flow-based methods are considered the most reliable. Under this category, two fundamental approaches are employed: steady-state and dynamic pseudos.…”
Section: Importance Of Upscalingmentioning
confidence: 99%